2018
DOI: 10.1016/j.ijcard.2018.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between QRS duration and incident atrial fibrillation

Abstract: In this large population-based study, QRSd was an independent predictor of incident AF among women, but not in men. Further studies are needed to better understand the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Most of the considered parameters have a clinical significance and a prognostic role with respect to the appearance of atrial fibrillation, sudden cardiovascular death, and major cardiovascular events [32][33][34], so their precise characterization is crucial. This work demonstrated, in a large contemporary primary population, that ECG is influenced by ageing, sex, cardiovascular diseases, and comorbidities but is difficult to be defined the weight of each of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the considered parameters have a clinical significance and a prognostic role with respect to the appearance of atrial fibrillation, sudden cardiovascular death, and major cardiovascular events [32][33][34], so their precise characterization is crucial. This work demonstrated, in a large contemporary primary population, that ECG is influenced by ageing, sex, cardiovascular diseases, and comorbidities but is difficult to be defined the weight of each of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In PRS analyses, we observed decreased risk of AF with increasing QT and QRS PRSs. This is an opposite direction of effect compared with epidemiological studies using directly measured ECG intervals where an increase in QRS or QT was associated with an increased risk of AF [75][76][77] . However, this relationship may be J-shaped as reported in a large study of over 280K individuals, and an increased risk of AF is also observed in patients with short QT syndrome compared to the general population 78,79 .…”
Section: Myocardial Fibrosis Impairs Cardiac Electrical Conduction Which Increases the Risk For Arrhythmogenesismentioning
confidence: 68%
“…30 QRS duration was an independent predictor of NOAF in this study, which was in concordance with previous findings. 31,32 The right and left atrium are composed of overlapping myocytes in the form of myocardial fibers that come together and create the atrial walls. Structural changes in the myocardium coexist in the atria and the ventricles, including cardiomyocyte hypertrophy and fibrosis; thus, QRS duration may be an indirect marker for left atrial disease.…”
Section: Commentsmentioning
confidence: 99%